PENGEMBANGAN MEDIA SMART BOX DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN - Nur Adiyah Yuliastri; Rohyana Fitriani; Baiq Shofa Ilhami (Jurnal CARE (Children Advisory Research and Education), 2021)
Abstract This study aims to develop smart box media and improve cognitive abilities of children aged 5-6 years. This research and development refers to the steps developed by Borg & Gall. The development design is simplified into 6 steps, namely: (1) research and information gathering, (2) planning, (3) developing the initial form of the product, (4) limited trials, (5) product revision, (6) field trials. The subjects of the field trial were 15 children. Data collection uses the validity of expert judgment and observation sheets. The data analysis technique uses a scale of five. The results showed that the smart box media from the material and appearance according to the expert (expert judgment) was in the "good" category and the media display was in the "very good" category. There is a difference in the values before and after the smart box media results, namely 41% began to develop before using the smart box media and after using the results obtained 80.4% developed very well. These results indicate that smart box media can improve children's cognitive development.Abstrak Penelitian ini bertujuan mengembangkan media smart box dan meningkatkan kemampuan kognitif anak usia 5-6 tahun. Penelitian dan pengembangan ini mengacu pada langkah yang dikembangkan oleh Borg & Gall. Desain pengembangan disederhanakan menjadi 6 langkah, yaitu: (1) penelitian dan pengumbulan informasi, (2) perencanaan, (3) mengembangkan bentuk awal produk, (4) ujicoba terbatas, (5) revisi produk, (6) ujicoba lapangan. Subjek uji coba lapangan adalah 15 orang anak. Pengumpulan data menggunakan validitas expert judgment dan lembar observasi. Teknik analisis data menggunakan skala lima. Hasil penelitian menunjukkan media smart box dari materi dan tampilan menurut ahli (expert judgment) berkategori “baik” dan tampilan media berkategori “sangat baik”. Terdapat perbedaan nilai sebelum dan sesudah media smart box hasil yaitu 41% mulai berkembang sebelum menggunakan media smart box dan sesudah menggunakan diperoleh hasil 80,4% berkembang sangat baik. Hasil tersebut menunjukkan bahwa media smart box dapat meningkatkan perkembangan kognitif anak.